A severe case of PLOD1‐related kyphoscoliotic Ehlers–Danlos syndrome associated with several arterial and venous complications: A case report. Issue 2 (27th February 2023) - Foy, Malika; Métay, Corinne; Frank, Michael; Denarié, Nicolas; Adham, Salma; Billon, Clarisse; Legrand, Anne; Jeunemaitre, Xavier; Gillas, Fabrice; Gaudon, Karen; De Mazancourt, Philippe; Mekki, Ahmed; et al.
Abstract: Kyphoscoliotic Ehlers–Danlos syndrome (kEDS) is a rare genetic disorder combining congenital hypotonia, congenital/early onset and progressive kyphoscoliosis, and generalized joint hypermobility. Vascular fragility is another characteristic of the disease rarely described. We report a severe case of kEDS‐PLOD1 with several vascular complications leading to difficulties in disease management. Abstract : This case report corroborates the increased risk of vascular complications in patients with PLOD1 ‐related kyphoscoliotic Ehlers–Danlos syndrome complicating disease management.